Teknologi Crowdfunding dalam Kegiatan Penggalangan Dana Sosial Berbasis Internet di Indonesia (Studi Pada Situs Kitabisa.com) - Risya Firdaus; Ridwan Roy Tutupoho (Jurusan Administrasi Niaga Politeknik Negeri Jakarta, 2022)
Fundraising activities are very close among the people of Indonesia. Rooted in the value of gotong royong and religious values ​​that encourage an individual to be able to share with fellow human beings and help each other. With the development of information and communication technology, it can make it easier for individuals to channel or raise funds. One of the technologies used in fundraising activities is crowdfunding. Crowdfunding makes it easier for the public in fundraising activities by utilizing the internet. This study aims to discuss how crowdfunding technology can change communication and interaction patterns in fundraising activities. This research is a literature study that uses descriptive qualitative methods. The result of this research is that there is a change in the pattern of communication and interaction in fundraising activities in Indonesian society with the presence of crowdfunding.